Influence of the Processing on the Ionic Conductivity of Solid-State Hybrid Electrolytes Based on Glass-Ceramic Particles Dispersed in PEO with LiTFSI. Issue 12 (7th September 2020) - Samsinger, R. F.; Schopf, S. O.; Schuhmacher, J.; Treis, P.; Schneider, M.; Roters, A.; Kwade, A.
Abstract : For the first time, glass-ceramic particles (LATP and LLZO) have been processed with both a tumbling-mixer and a kneader on semi-industrial scale. Although sintered LATP and LLZO discs reveal a statistically negligible ionic interface resistance to PEO with LiTFSI, the total conductivity of dispersed particles within a PEO-LiTFSI matrix is only slightly enhanced at 80 °C. However, for a tumbling mixing process, SEM investigations prove insufficient contact of particles within the matrix as well as agglomerates, cracks and voids. With the shear intensive kneader, dense and homogeneous samples were obtained. Compared to nanometer-sized SiO2 particles, the LATP filler enable an increase of the ionic conductivity of the hybrid PEO system by a factor of about two. These finding help to overcome solvent-based mixing processes that may cause uncontrolled decomposition and surface reactions of filler particles thereby changing microscopic conduction mechanisms in the hybrid electrolytes.